Multigene panel next generation sequencing in a patient with cherry red macular spot: Identification of two novel mutations in NEU1 gene causing sialidosis type I associated with mild to unspecific biochemical and enzymatic findings - Mütze, Ulrike; Bürger, Friederike; Hoffmann, Jessica; Tegetmeyer, Helmut; Heichel, Jens; Nickel, Petra; Lemke, Johannes; Syrbe, Steffen; Beblo, Skadi (Molecular genetics and metabolism reports, 2017)
Background: Lysosomal storage diseases (LSD) often manifest with cherry red macular spots. Diagnosis is based on clinical features and specific biochemical and enzymatic patterns. In uncertain cases, genetic testing with next generation sequencing can establish a diagnosis, especially in milder or atypical phenotypes. We report on the diagnostic work-up in a boy with sialidosis type I, presenting initially with marked cherry red macular spots but non-specific urinary oligosaccharide patterns and unusually mild excretion of bound sialic acid. Methods: Biochemical, enzymatic and genetic tests were performed in the patient. The clinical and electrophysiological data was reviewed and a genotype-phenotype analysis was performed. In addition a systematic literature review was carried out. Case report and results Cherry red macular spots were first noted at 6years of age after routine screening myopia. Physical examination, psychometric testing, laboratory investigations as well as cerebral MRI were unremarkable at 9years of age. So far no clinical myoclonic seizures occurred, but EEG displays generalized epileptic discharges and visual evoked potentials are prolonged bilaterally. Urine thin layer chromatography showed an oligosaccharide pattern compatible with different LSD including sialidosis, galactosialidosis, GM1 gangliosidosis or mucopolysaccharidosis type IV B. Urinary bound sialic acid excretion was mildly elevated in spontaneous and 24h urine samples. In cultured fibroblasts, α-sialidase activity was markedly decreased to <1%; however, bound and free sialic acid were within normal range. Diagnosis was eventually established by multigene panel next generation sequencing of genes associated to LSD, identifying two novel, compound heterozygous variants in NEU1 gene (c.699C>A, p.S233R in exon 4 and c.803A>G; p.Y268C in Exon 5 in NEU1 transcript NM_000434.3), leading to amino acid changes predicted to impair protein function. Discussion Sialidosis should be suspected in patients with cherry red macular spots, even with non-significant urinary sialic acid excretion. Multigene panel next generation sequencing can establish a definite diagnosis, allowing for counseling of the patient and family.